Service quality towards customer loyalty in Malaysia's domestic low cost airline service - Muhamad Yunus, Nor Sara Nadia; Bojei, Jamil; Wan Rashid, Wan Edura (International Academy Publishing, 2013)
Delivering high quality service to the passengers is imperative so that airline companies can survive and strengthen their competitiveness. Even though there have been extensive research on service quality and customer loyalty in the past, little study has been conducted in this specific area. Hence, this paper aims to propose a conceptual framework on service quality and its relationship towards customer loyalty among Malaysia’s domestic low cost airline services passengers. Reliability, tangibles, responsiveness, assurance and empathy are considered as critical dimensions of service quality that possibly provide empirical evidence in relation to customer loyalty. Subsequently, the consequences of the customer loyalty are further elaborated in this paper too. It is expected that the findings of this study can assist the organization to deliver high service quality to the customers and enhancing customers’ satisfaction in fulfilling their needs and wants. More importantly, improving service quality in such an organization may result in long-term increase in customer’s loyalty; this in turn leads to cost savings and improved profitability and market share.